A numerical investigation of film cooling performance through variations in the location of discrete sister holes. (25th August 2016) - Khajehhasani, Siavash; Jubran, Bassam A.
Highlights: Variation of sister holes location for film cooling is numerically investigated. Streamwise variations have insignificant effect on film cooling effectiveness. Spanwise variations have significant effect on film cooling effectiveness. Farther spanwise locations increases the lateral spread of the coolant. Abstract: In the present paper, a numerical parametric study on the effects of the discrete sister holes' location on film cooling performance is carried out. The location of the up/downstream combination of the sister holes has been changed individually in the streamwise and spanwise directions. These include five new locations in each direction. The simulations are performed using three-dimensional Reynolds Averaged Navier-Stokes (RANS) analysis with the realizable k – ε model combined with the standard wall function. Simulations are performed for low and high blowing ratios, where the low blowing ratios are represented by M = 0.2 and 0.5, and the high blowing ratios by M = 1.0 and 1.5. It is found that the streamwise variations in the location of the sister holes do not provide a significant change in the adiabatic film cooling effectiveness results. On the other hand, the effectiveness results are considerably improved for the spanwise variations. For example, the laterally averaged effectiveness results for a case where the sister holes were positioned at the spanwise location of z/D = ±1 is increased about 78% and 49% as compared to the base case (z/D = ±0.75) for the blowing ratios of 1 and 1.5, respectively. Moreover, as a result of the anti-counter rotating vortices generated from the sister holes and the repositioning of the sister holes, the jet lift-off effect has considerably decreased and more volume of coolant is distributed in the spanwise direction.